KORELASI ANTARA PENAMBAHAN ASPAL MINYAK PADA CAMPURAN PERKERASAN ASPAL BETON HASIL DAUR ULANG TERHADAP KARAKTERISTIK MARSHALL - Ansyori Alamsyah, Alik (Jurnal Gamma, 2012)
Korelasi Antara Penambahan Aspal Minyak Pada Campuran Perkerasan Aspal Beton Hasil Daur Ulang Terhadap Karakteristik MarshallAlik  Ansyori  AlamsyahStaf Pengajar Jurusan Teknik Sipil, Fakultas TeknikUniversitas Muhammadiyah MalangEmail: alik.syah@yahoo.comABSTRACTImproved  road  by  adding  extra  layers  of  constant  thickness  will  result  in increasingly thick layers of pavement and materials needed thining. Treatment with pavement  recycling  technologies  (recycling)  is  an  alternative  to  overcome  this problem because it has several  advantages such as to restore power and maintain the geometric road pavement and overcome dependence on new material. Recycling processed and supported by adequate equipment will  produce a mixture that can offset the value structure of the mixture. The addition of new  materials and or additional  materials  in the  former  material  scratching  the  old  pavement  is  one alternative to increase the carrying capacity of ex-scratching material.Research conducted at the Laboratory of Highway Muhammadiyah University of Malang. The quality of asphalt concrete recycled with the addition of new asphalt can be known through the Marshall test results (stability, flow plastically, the results for the marshall, and the cavity in the mix). The binder used was 60/70 penetration bitumen with each variation with the addition of 0.5%, 1%, 1.5%, 2%, and 2.5%. From the result showed that the addition of new asphalt on a mixture of  recycled asphalt to improve the power tie. Optimum asphalt content based on the value of stability, flow, and Marshall Quotient amounted to 7.25% of the total weight of the mixture, then there was  an increase of 0.45% asphalt needs of optimum asphalt content of 6.8%.Keywords : Marshall stability, recycling, asphalt.